Four Weeks of Inspiratory Muscle Training Improves Self-Paced Walking Performance in Overweight and Obese Adults: A Randomised Controlled Trial. (26th June 2012) - Edwards, A. M.; Maguire, G. P.; Graham, D.; Boland, V.; Richardson, G.
Abstract : Objective. To examine whether a programme of inspiratory muscle training (IMT) improves accumulative distance of self-paced walking in overweight and obese adults. Methods. A total of 15 overweight and obese adults were randomized into experimental (EXP: n = 8 ) and placebo (PLA: n = 7 ) groups. Lung function, inspiratory muscle performance, 6-minute walking test, and predicted V ˙ O2 max were assessed prior to and following the 4-week IMT intervention. Both groups performed 30 inspiratory breaths, twice daily using a proprietary inspiratory resistance device set to 55% of baseline maximal effort (EXP), or performing the same inspiratory training procedure at the minimum resistive setting (PLA). Results. Lung function was unchanged in both groups after-training; however inspiratory muscle strength was significantly improved in EXP (19 ± 25.2 cm H2 O gain; P < 0.01 ) but did not significantly change in PLA. Additionally, the posttraining distance covered in the 6-minute walking test was significantly extended for EXP (62.5 ± 37.7 m gain; P < 0.01 ), but not for PLA. A positive association was observed between the change (%) of performance gain in the 6-minute walking test and body mass index (r = 0.736 ; P < 0.05 ) for EXP. Conclusion. The present study suggests that IMT provides a practical, minimally intrusive intervention to significantly augment both inspiratory muscle performance and walking distance covered by overweight and obese adults in a clinically relevant 6-minute walk test. This indicates that IMT may provide a useful priming (preparatory) strategy prior to entry in a physical training programme for overweight and obese adults.